Implementing Big Data Management on Grid Computing Environment (International Journal of Engineering and Computer Science, 2014)
With the current advances of today's technology in many sectors such as manufacturing, business, science and web application, a variety of data to be processed continues to witness an exponential rise. This data is referred to as big data. Efficient management and processing of this data poses an interesting but significant problem. To utilize the numerous benefits of grid computing, Big data processing and management techniques should be integrated in the current grid environment. In this paper, the definition, features and requirements of big data platform are explored. Incorporating Hadoop is suggested as it the most commonly used technique in handling Big Data as it offers reliability, ease of use, ease of maintenance and scalability.